Incomplete ecdysis syndrome in adult males of Cryphiops caementarius (Crustacea: Palaemonidae) and its consequences in intensive culture - Reyes, Walter (2018)
The aim of the study was to describe the stages of the incomplete ecdysis syndrome in adult shrimp males Cryphiops caementarius captured in the Pativilca River (Lima, Peru), as well as to evaluate its consequences in intensive culture. Fifty-four adult shrimp that had complete cephalothoracic appendages were collected. The molting stages were observed twice a week and those close to the ecdysis were observed daily without being manipulated. The results of the observations allowed to classify the incomplete ecdysis syndrome (E) in five substages: E1: Body and appendages trapped with its exuvia, which led to the death of shrimp. E2: Cephalothorax and cephalothoracic appendages trapped with its exuvia, which led to the death of shrimp. E3: Pereopods trapped with their exuvia, which led to the death of the shrimp. E4: Both chelipods trapped with their exuvia, whose death or survival of the shrimp depended on the autotomization of the chelipods. E5: A single chelipod (major or minor) trapped with its exuvia, whose death or survival of the shrimp depended on the autotomization of the chelipod. Incomplete ecdysis syndrome affected survival and yield.